Pengaruh E-System Pajak, Self Assessment dan Pemahaman Perpajakan Terhadap Kepatuhan Wajib Pajak Orang Pribadi - Zinny, Haffiz; Ahmad, Afridian Wirahadi; Zerma, Desi Handayani (Accounting Information System, Taxes and Auditing Journal (AISTA Journal), 2024)
This research aims to examine the influence of the tax e-system, self-assessment, and tax understanding on the compliance of individual taxpayers who own restaurant businesses in the city of Padang. Data collection method for this research involves primary data by distributing questionnaires directly to the respondents. The population in this study consists of all restaurant taxpayers in Padang who are registered with BAPENDA Padang. The sampling technique used is simple random sampling with a 10% error rate according to the Slovin formula. The sample in this study consists of 83 individual taxpayers who own restaurant businesses. The data analysis method employed is multiple linear regression. The results of this study indicate that the tax e-system and self-assessment have an influence on the compliance of individual taxpayers. However, tax understanding does not have an influence on the compliance of individual taxpayers.